Asymptotic energy of connected cubic circulant graphs. Issue 1 (2nd January 2021) - Bulut, Alper; Hacioglu, Ilhan
Abstract: In this article, we compute the oblique asymptote of the energy function for all connected cubic circulant graphs. Moreover, we show that this oblique asymptote is an upper bound for the energies of two of the subclasses of Möbius ladder graphs and lower bound for the remaining four subclasses.